Critical aspects of pulse current GMA welding of stainless steel influencing metallurgical characteristics. (2017) - Kulkarni, Shrirang G.; Agrawal, B.P.; Ghosh, P.K.; Ray, Subrata
Metallurgical characteristics of the weld of austenitic stainless steel (ASS) has been studied as a function of pulse parameters, heat input and heat transferred to the weld pool in pulsed current gas metal arc welding (P-GMAW) process. The combined influence of these three aspects on microstructure and hardness of weld bead and the heat affected zone has been thoroughly investigated. Intergranular corrosion susceptibility of heat affected zone of different weld has also been investigated. The characteristics of pulse current gas metal arc weld have been compared with conventional gas metal arc welds at similar heat inputs. The pulse parameters are suggested which will produce superior quality relative to gas metal arc welding (GMAW) as a research goal. The superiority of pulse current gas metal arc weld has been justified.